Установка толстослойного анодирования алюминия - Сокол, В.А.; Игнашев, Е.П. (Технология и конструирование в электронной аппаратуре, 2003)
С целью повышения эффективности охлаждения пластин при получении оснований из анодированного алюминия предложено производить процесс толстослойного анодирования при непрерывном движении пластин. На этом принципе создана установка динамического анодирования, которая обеспечивает получение оксидных слоев толщиной до 0,4 мм на основаниях размерами от 48×60 мм до 100×100 мм и подложек из свободного анодного оксида толщиной до 1 мм с высокими физико-механическими свойствами без разрыхления оксида. As a rule, in the devices used for obtaining bases out of anodized aluminium the deprivation of the plates of Joule heat during anodizing is carried out by a static electrolyte. That, however, doesn't necessarily lead to plates' overheating and etching of the oxide layer. In order to increase the efficiency of plates' coding it is proposed to carry out thick-wall anodizing parallel with their continuous motion. This principle is laid into basis of a dynamic anodizing device,which provides oxide layers up to 0,4 mm thick and having dimensions from 48×60 up to 100×100 mm, as well as the base plates up to 1 mm thick, having strong and weak mechanical properties, causing no oxide loosening.
As a rule, in the devices used for obtaining bases out of anodized aluminium the deprivation of the plates of Joule heat during anodizing is carried out by a static electrolyte. That, however, doesn't necessarily lead to plates' overheating and etching of the oxide layer. In order to increase the efficiency of plates' coding it is proposed to carry out thick-wall anodizing parallel with their continuous motion. This principle is laid into basis of a dynamic anodizing device,which provides oxide layers up to 0,4 mm thick and having dimensions from 48×60 up to 100×100 mm, as well as the base plates up to 1 mm thick, having strong and weak mechanical properties, causing no oxide loosening.